Ripensare l’estetica nel tempo “mostruoso” - Mottana, Paolo (Studi sulla Formazione/Open Journal of Education, 2015)
The text reads again the notion of esthetic above all as symbolic sensibility, sensibility to the secret language of world, to her intimate correspondences, to the network of affinity in which it’s interweaved. Today this sensibility appears secondary and anesthetized, with effects of decline that reflect in many aspects of our life. It’s necessary to reactivate as soon as possible this sensibility and the resulting responsibility through the exercise of an accurate and receptive look, that is central in pedagogy of imagination and in general in artistic practicality. Only by virtue of an improved familiarity with the creative practicality of art in all its educational forms will be possible to give back slowly to man the necessary sensibility to listen the mute message of world and to learn again to inhabit it without violate it.